Lieb-Robinson bounds for open quantum systems with long-ranged interactions - Sweke, Ryan; Eisert, Jens; Kastner, Michael (Journal of Physics A: Mathematical and Theoretical, 2019)
We state and prove four types of Lieb-Robinson bounds valid for many-body open quantum systems with power law decaying interactions undergoing out of equilibrium dynamics. We also provide an introductory and self-contained discussion of the setting and tools necessary to prove these results. The results found here apply to physical systems in which both long-ranged interactions and dissipation are present, as commonly encountered in certain quantum simulators, such as Rydberg systems or Coulomb crystals formed by ions.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Lieb-Robinson bounds; Lindblad dynamics; long-range interactions; open quantum systems